Content triggering system using tricolor LED strips and Optical Camera Communication in Rolling Shutter mode - Georlette, Veronique; Piras, Florian; Jurado-Verdu, Cristo; Bette, Sebastien; Point, Nicolas; Moevaert, Veronique (2021 Third South American Colloquium on Visible Light Communications (SACVLC), 2021)
Optical Camera Communication (OCC) technology uses Light Emitting Diode (LED) light sources as a transmitter and a camera as a receiver. This emerging technology is very interesting for indoor and outdoor geolocation applications. Indeed, cities and museums can offer interactive tours where users can use their cameras to sense a code and watch appropriate stored content depending on the location. In this context, this paper proposes a simple, fast, and efficient OCC system. It uses RGB (Red-Green-Blue) LED strips to replace the classical white LED, with the aim to highly increase the potential number of location codes sent to the user. The use of a light diffuser is studied to enhance the image issued from the rolling shutter mode, and an operational image signal processing algorithm is described. This paper also proposes practical guidelines to take into account when designing such a system.